Ethical problems of repetitive research (1977)
The Working Group in Current Medical/Ethical Problems, which has presented this report, was originally set up in March 1973, and operates under the auspices of the Northern Regional Health Authority. The present members of the group are: The Rt Revd Dr J S Habgood, Lord Bishop of Durham (chairman); Mrs J M Burrow, lay member; Mr W O H Collins, retired administrator; The Rt Revd Mgr P Loftus, President, Ushaw College, Durham; Dr J M Parkin, consultant paediatrician; Dr G O Richardson, consultant physician; Miss D Turnbull, regional nurse, personnel; Professor J H Walker, University Department of Family and Community Medicine. The following gave evidence to the group during the preparation of the report: Professor R Hall; Professor I D A Johnston; Professor D N S Kerr; Dr F J W Miller; Professor A M Thomson; Professor S Shuster.